First report of twig blight disease of green pea caused by Choanephora infundibulifera in India - SANJIB PRASAD KUIRY and BHOLANATH MANDAL, SIDDHARTHA DAS, SUBRATA DUTTA* (Indian Phytopathology, 2017)
The present report describes Choanephora infundibulifera as causal pathogen of twig blight disease of Pisum sativum recorded from the Gangetic alluvial region of West Bengal, India, in September 2015. Severe disease infestation with the initiation of shoot apical meristem, leaf, blossom blight was observed. The monsoon season (June-September) with optimum temperature (28-30Â°C) and high moisture (80-90%) level was found to enhance the disease progress. The pathogen was identified based on its cultural, morphological, and the internal transcribed spacer (ITS) - r DNA sequence analysis. To our understanding, this pathogen is being described for the first time as causal agent of twig blight disease of pea in India.